(untitled) (MAUSAM, 1987)
The heat and moisture budgets of the atmosphere (surface to 100 mb) over the central equatorial Indian Ocean (2°N to 2° S; 76°E to 800E) have been investigated utilising the surface and upper air data collected on board four Russian ships durin.8 summer monsoon days (25 to 31 July 1977). The time, mean net flux divergences of latent heat and dry static energy are round to be about –0.366 and –0.471 x 1013 cal/sec respectively in the study area. Contributions from the eddy term are in general higher for heat budget than those for moisture budget. The budget estimates of mean rates or radiational cooling and precipitation for the observational period are found to be 0.70°C and 6, 7 mm/day respectively which are comparable with the climatological values.